Myotonic Dystrophy Initially Presenting as Tachycardiomyopathy Successful Catheter Ablation of Atrial Flutter. (24th August 2010) - Asbach, S.; Gutleben, K. J.; Dahlem, P.; Brachmann, J.; Nölker, G.
Abstract : Myotonic dystrophy is a genetic muscular disease that is frequently associated with cardiac arrhythmias. Bradyarrhythmias, such as sinus bradycardia and atrioventricular block, are more common than tachyarrhythmias. Rarely, previously undiagnosed patients with myotonic dystrophy initially present with a tachyarrhythmia. We describe the case of a 14-year-old boy, who was admitted to the hospital with clinical signs and symptoms of decompensated heart failure and severely reduced left ventricular function. Electrocardiography showed common-type atrial flutter with 2 : 1 conduction resulting in a heart rate of 160 bpm. Initiation of medical therapy for heart failure as well as electrical cardioversion led to a marked clinical improvement. Catheter ablation of atrial flutter was performed to prevent future cardiac decompensations and to prevent development of tachymyopathy. Left ventricular function normalized during followup. Genetic analysis confirmed the clinical suspicion of myotonic dystrophy as known in other family members in this case.